دراسة بعض المواصفات المورفولوجية والكيميائية لثمار عدة أصناف من الإكدنيا (Eriobotrya Japonica) - أبو الشملات ربى (Latakia University Journal -Biological Sciences Series, 2017)
نفذت الدراسة خلال فترة (2014-2015) في محافظة اللاذقية. وقد استخدم في هذه الدراسة ثلاثة أصناف من الإكدنيا وهي الصيداوي والمغربي والبلدي. تم توصيف شكلي للثمار وحساب متوسط وزن الثمرة ومتوسط عدد البذور في الثمرة، كما أجريت بعض التحاليل الكيميائية للعصير. خضعت البيانات للتحليل الإحصائي وأظهرت النتائج التالية: أبكر موعد لنضج الثمار وجد عند الصنف البلدي. بلغ أعلى معدل لمتوسط وزن الثمرة (53.40غ) في الصنف المغربي، وتراوح شكل الثمرة بين البيضوي عند الصنف المغربي والصيداوي والشكل الكروي عند الصنف البلدي. كما تفوق الصنف المغربي والصيداوي في كمية الإنتاج (34.67،34 كغ/شجرة) على التوالي على الصنف البلدي. بلغت أعلى نسبة لفيتامين C والحموضة والسكريات عند الصنف البلدي (0.977، 1.073، 15.20%) على التوالي. The study was excuted in Latakia governorate during the period (2014-2015). In this study, it has been used three cultivars of Eriobotrya japonica which were Seedawi, Morocan and Municipal). Onfigurable characterization, the average fruit weight calculation and the average number of seeds have been done of the fruit. Some chemical analysis were also conducted of the juice. The data has been statistical analyzed and the results showed that the earliest cultivar in maturity was Municipal. The highest rate of average fruit s weight was (53.40g) in Morocan cultivar. And the fruits shapes were between the oval shape in the Morocan and Seedawi cultivar, and circular shape in the Municipal cultivar. The Morocan and Seedawi cultivars have the supremacy in production quantity(34.67-34 kg/tree) respectively at the Municipal. The highest proportion was in vitamin C, the acidity and sugars were (0.977,1.073,15.20 %) respectively in municipal cultivar.